PENGEMBANGAN MODUL BERBASIS MASALAH PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL UNTUK SISWA KELAS VII MTsN I MATUR KABUPATEN AGAM - Silvia, Rizky - (Pendidikan Matematika, 2014)
Teaching materials is an important part of learning because it can be used as a learning resource for teachers and students. Teaching materials which are expected to guide students to learn independently, understandable easily by students, communicative language with students and improve students problem solving abilities. Existing textbooks have not been able to guide students to a concept and solve mathematical problems. Therefore, it needs to develop teaching materials in the form of module based on a material issue of linear equations and inequalities of one variable. Type of this research is the development of the 4-D model. However, this study only performed three stages such as; the definition, the design phase and the development phase. Based on the result of module-based validity that has been done by the validator, it shows that problem-based module on the criteria is very valid issue, namely 3.47. The result of practicalities test that has been done by teachers and students indicate that the problem-based module on the category is very practical, namely 86%.